2021
DOI: 10.4293/jsls.2020.00078
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Surgical Stress and Biochemical Recurrence After Robotic Radical Prostatectomy

Abstract: Background and Objectives: This study was conducted to identify whether surgical stress during the peri-operative period of robot-assisted radical prostatectomy might affect biochemical recurrence in patients with positive surgical margins.Methods: Participants in the present study were 324 consecutive patients with localized prostate cancer who underwent robot-assisted radical prostatectomy between February 2013 and June 2018. Positive surgical margins were diagnosed in 61 of them. Patients with positive surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…One conclusion that can be drawn from the study by Choo et al 82 is that similar PSM rates do not imply similar BCR rates. In addition, Meguro et al 83 reported that in multivariate analyses, operative time was significantly associated with BCR, with a cut-off value of 228.5 min for operative time. They suggested that prolonged operative time was associated with BCR in patients with positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…One conclusion that can be drawn from the study by Choo et al 82 is that similar PSM rates do not imply similar BCR rates. In addition, Meguro et al 83 reported that in multivariate analyses, operative time was significantly associated with BCR, with a cut-off value of 228.5 min for operative time. They suggested that prolonged operative time was associated with BCR in patients with positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that surgery creates a state of physical trauma and physiological stress that triggers cellular immune dysfunction ( 13 , 14 ). Our group and others have shown that the postoperative period represents a unique time frame of immunosuppression that can be hijacked by a tumor for its survival advantage in different cancer types ( 15 18 ). However, the idea of surgery-induced immunosuppression as a facilitator of recurrence and metastatic spread has not been explored in the context of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 97%